Main reasons why bachelor of arts in modern languages with the specialty in french and english and bachelor of arts in english oriented to teaching students of the Foreign Language Department at the University of El Salvador drop out their studies - Alvarenga Najarro, Jennie Lisseth; Merino Orellana, Fátima Lissette; Llanes Márques López, Jorge Homero; Edgar, Nicolás Ayala (San Salvador, El Salvador : Universidad de El Salvador, 2014)
Furthermore, at the University of El Salvador, specifically in the majors of Bachelor of Arts in Modern Languages with the Specialty in French and English and the Bachelor of Arts in English Oriented to Teaching, the problem of dropping out has increased in the last two years. That is why the researchers have decided to investigate about the main reasons why students of the majors mentioned above have chosen dropping out their majors. For the sake of economy, the major Bachelor of Arts in Modern Languages with the Specialty in French and English will be referred to as BA in Modern Languages, whereas the Bachelor of Arts in English Oriented to Teaching will be termed BA in English in the following considerations. Education is the action of being educated, so this process becomes a right for all the people and all nations. When students drop out of their majors, the course of their lives may be totally reset. People that drop out typically earn less than their peers with more education. Researches show two sets of factors which may be predictors of whether students will drop out or graduate from university: One set is associated with the institutional characteristics of their families, classroom environment, and communities; the other set is associated with the individual characteristics of the students themselves like dissatisfaction of expectations, emotional issues and economic conditions that influence students’ decisions to drop out in several ways. In the following section we will analyze in depth all personal, family, institutional and social elements that have been identified as the participating variables involved in the educational process causing a student to abandon his/her studies. For example, studies show that students living with both parents have lower dropout rates and higher graduation rates as compared to students in other living circumstances.
Anexos.
Bibliográfia : hojas 62
Keywords: inglés -- Enseñanza